REGARDING THE RESULTS OF SCIENTIFIC RESEARCH CONDUCTED BY THE JOINT UZBEK-CHINESE INTERNATIONAL ARCHAEOLOGICAL EXPEDITION IN MINGTEPA CITY RUINS (Scientific journal of the Fergana State University, 2024)
This article presents scientific data from archaeological research carried out jointly by the Uzbek-Chinese international archaeological expedition on the ruins of Mingtepa, which is a major archaeological site of the ancient period of the Fergana Valley. During the expedition, results were obtained about the structural structure of the city (arch, inner city and outer city), stratigraphy of material cultural layers, defense system and information about the crafts, art, customs and religious beliefs of the people who lived here.